New aspects of microbial vitamin K2 production by expanding the product spectrum - Zhang, Zimeng (Microb Cell Fact, 2021)
Vitamin K2 (menaquinone, MK) is an essential lipid-soluble vitamin with critical roles in blood coagulation and bone metabolism. Chemically, the term vitamin K2 encompasses a group of small molecules that contain a common naphthoquinone head group and a polyisoprenyl side chain of variable length. Among them, menaquinone-7 (MK-7) is the most potent form. Here, the biosynthetic pathways of vitamin K2 and different types of MK produced by microorganisms are briefly introduced. Further, we provide a new aspect of MK-7 production, which shares a common naphthoquinone ring and polyisoprene biosynthesis pathway, by analyzing strategies for expanding the product spectrum. We review the findings of metabolic engineering strategies targeting the shikimate pathway, polyisoprene pathway, and menaquinone pathway, as well as membrane engineering, which provide comprehensive insights for enhancing the yield of MK-7. Finally, the current limitations and perspectives of microbial menaquinone production are also discussed. This article provides in-depth information on metabolic engineering strategies for vitamin K2 production by expanding the product spectrum.